Information and Communication Technology for Dissemination of Agricultural Information in Hills: A Critical Overview (Indian Journal of Extension Education, 2018)
The farmers of the hill region are facing serious difficulties altogether with the lack of information dissemination channels. This is highly attributed to the geographical disadvantages of distantly located hamlets and fragmented household of hills. ICThas a significant role in bridging the gap of information dissemination in hills. In the present study an attempt has been made to delineate the role of ICT in dissemination of agricultural information among hill farmers in terms of sources of getting agriculture information, purposes of using ICT tools, networking with other stakeholders through ICT, usefulness of information received through ICT tools, and benefits and problems in using ICT tools in hills. The study was conducted in Mahatgaon cluster of Hawalbagh block in Almora district, Uttarakhand taking a random sample of 100 farmers. The data was collected by a pre-tested structured interview schedule through personal interview method. The study revealed that most of the respondents often received agriculture information from research and extension institutes working in the area like ICAR-VPKAS, KVK- Matela and GBPIHED (82%) followed by government and public departments (60%) and university like GBPUA&T (45%). It was reported that the main purposes of using ICT tools were for getting information about the weather (99%), farm advice (99%) and market (97%). Mobile was found to be the most used medium of networking with the stakeholders (up to 75%). Farmers perceived that farm advice and weather information received through ICT tools were most useful (80%). Easy access to information and lack of awareness were identified to be main benefit and problem of using ICTtools in hills, respectively.